Essentials of Menopause Management A Case-Based Approach - Pal, Lubna; Sayegh, Raja A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Removing the shroud of complexity that had engulfed the field of menopause research and management for more than a decade, this unique, case-based resource discusses a range of topics relevant to the reproductive health of the aging female. The opening section includes chapters covering the symptomatology, epidemiology and impact of the menopausal burden, and reviews in depth the most current evidence on the efficacy, risks and benefits of pharmacological and alternative therapies. Utilizing vibrant case material, the second section details common symptoms of menopause and an individualized approach to management, such as sleep loss, skeletal fragility, sexual dysfunction, hirsutism and alopecia, primary ovarian insufficiency and failure, and vasomotor symptoms. Chapters reviewing therapeutic options and considerations tailored to gynecologic and breast cancer patients and survivors comprise the third and final section. Developed as a multidisciplinary collaboration and addressing the needs of practicing reproductive medicine clinicians and researchers providing care to an aging female population, Essentials of Menopause Management provides clear, up-to-date information and recommendations on the range of current treatment strategies for menopause and its symptoms.
Part I: Symptomatology, epidemiology and impact of the menopausal burden, and review of evidence on the efficacy, risks and benefits of pharmacological and alternative therapies -- Reproductive Aging: Epidemiology, Symptomatology and Nomenclature -- Five Decades of Hormone Therapy Research: The Long, The Short and The Inconclusive -- Non-Hormonal Pharmacotherapies for Menopause Management -- Pharmacotherapies for Menopause Management: Hormonal options -- Management of Menopause and Perimenopause: Integrative Medicine in Support of Wellness -- Part II: An inferential and individualized approach to management of common menopausal concerns through clinical vignettes -- Clinical Management of Menopause-Related Sleep Disturbance -- Management of Genitourinary Syndrome of Menopause (GSM) in menopausal women -- Skeletal Fragility-a Common Menopausal Burden. Risk assessment, diagnosis and management -- Sexuality, Sexual dysfunction and Menopause -- The Case for Androgens in Menopause Management: When and how?- Post-Menopausal Alopecia (Hair Loss) -- Evaluation and Management of Hirsutism in Postmenopausal Women -- Primary Ovarian Insufficiency/Premature Ovarian Failure: Management Considerations and Strategies -- Surgical Menopause -- Vasomotor Symptoms & Medical Disorders -- Part III: Managing Menopause in Cancer Survivors -- Pharmacological Therapy for Vasomotor Symptoms in Breast Cancer Survivors -- Management of Osteoporosis in Postmenopausal Breast Cancer Survivors -- Management Strategies for Sexual Health after Breast Cancer Diagnosis -- Hormonal Therapy for Menopausal Symptoms in Gynecologic Cancer Survivors.
Keywords: Medicine; Gynecology; Endocrinology; Reproductive medicine; Medicine & Public Health; Reproductive medicine; Gynecology; Endocrinology